The Development of Cities. From al-‛Ubaid to the End of Uruk 5. Part 1 und Part 2 - Mallowan, M. E. L. (1967)
САН Revised Edition Vol. I, Chapter VIII = fasc. 58; I. Babylonia and Mesopotamia; II. Assyria; 10s 6d/$ 2.25; III. Syria; IV. Iran; 6s/$1.25; Wiederholung von 28:892.